Product Development Management in Improving the Competitive Advantage of SMEs - Arifin Djakasaputra; Valentina; Chennan Jessalonica (CV. Proaksara Global Transeduka, 2024)
The role of product development management is very important in improving business sustainability. When there is market saturation in existing products, it can be overcome through the emergence of new products, in the sense of expanding and supporting existing products. PKM activities aim to help MSMEs understand product development management in running a business, and maintain survival in the future. Activity partners are engaged in handicraft businesses, with the mada mute brand that provides handicraft products made from woll and beads. In its activities it faces various problems, especially in carrying out product development management, this is due to the lack of partner knowledge about matters related to product development PKM activities aim to help increase partner knowledge. The method offered in this activity is online training/socialization through Zoom meetings. The material to be presented includes: introduction to the concept of product development; product development process; new product development strategy; product life cycle strategy. The results of the activity show that the problems that arise in partner businesses are resolved, partners can understand the importance of new product development for business survival.